Usefulness of bounce-back admission in monitoring the quality of practice in the emergency department - Tarumi Y; Harada T; Saito T; Hiroshige J; Dohi K (Dove Medical Press, 2019)
Yoko Tarumi,1 Taku Harada,1 Tsukasa Saito,1 Juichi Hiroshige,1 Kenji Dohi21Department of General Medicine, Showa University, Tokyo 142-8555, Japan; 2Department of Emergency, Disaster and Critical Care Medicine, Showa University, Tokyo 142-8555, JapanBackground: Recently, unscheduled readmissions after discharge from the emergency department (ED) (bounce-back admissions, BBAs) have been monitored as a hospital performance measure in countries other than Japan. It has been suggested that BBAs may be caused by errors in diagnoses or treatments.Purpose: This retrospective cohort study aimed to evaluate BBAs and improve the quality of medical care in the ED of Showa University Hospital by analyzing the data of adult patients (≥18 years) with index visits to the ED of Showa University Hospital between June 2011 and May 2013 (n=15,069).Patients and methods: Patients were registered and followed up for unscheduled admissions to this hospital within 7 days. In order to understand the reasons for BBAs, individual diagnoses upon BBA were compared to the corresponding diagnoses upon discharge.Results: Among the 11,669 discharged patients, 180 patients were admitted within 3 days after discharge (3-day BBAs), and 257 were admitted within 7 days after discharge (7-day BBAs). The main diagnoses upon admission (BBA) were pneumonia or exacerbation of chronic obstructive pulmonary disease (COPD) or asthma (n=40, 16%), cholecystitis or cholangitis (n=21, 8.2%), and urinary tract infection (n=16, 6.2%). Among the 7-day BBA cases, 117 patients had similar and 110 patients had different diagnoses upon discharge and admission; in the remaining 30 cases, the results could not be ascertained owing to incomplete diagnostic data. In the cases of pneumonia, exacerbation of COPD or asthma, and colitis or enterocolitis, there was a significantly higher “similar” diagnoses than “different”, while the reverse was true for cases of stroke, ileus or bowel obstruction, and meningitis. These results were shared with the ED staff, and similar surveillances were periodically conducted. The frequency of admission within 7 days after discharge continuously declined from 2013 to 2016.Conclusion: Analyzing the discharge and admission diagnoses may help ED staff to understand the reasons for common errors in order to follow the plan-do-check-act cycle of medical care in the ED.Keywords: unscheduled admission after ED discharge, analysis of diagnosis, improvement of emergency care quality